A Tn7-Like Transposon Is Present in the glmUS Region of the Obligately Chemoautolithotrophic Bacterium Thiobacillus ferrooxidans - Oppon, Joseph C. (American Society for Microbiology, 1998)
The region downstream of the Thiobacillus ferrooxidans ATCC 33020 atp operon was examined, and the genes encoding N-acetylglucosamine-1-uridyltransferase (glmU) and glucosamine synthetase (glmS) were found. This atpEFHAGDC-glmUS gene order is identical to that of Escherichia coli. The T. ferrooxidans glmS gene was shown to complement E. coli glmS mutants for growth on minimal medium lacking glucosamine. A Tn7-like transposon, Tn5468, was found inserted into the region immediately downstream of the glmS gene in a manner similar to the site-specific insertion of transposon Tn7 within the termination region of the E. coli glmS gene. Tn5468 was sequenced, and Tn7-like terminal repeat sequences as well as several open reading frames which are related to the Tn7 transposition genes tnsA, tnsB, tnsC, and tnsD were found. Tn5468 is the closest relative of Tn7 to have been characterized to date. Southern blot hybridization indicated that a similar or identical transposon was present in three T. ferrooxidans strains isolated from different parts of the world but not in two Thiobacillus thiooxidans strains or a Leptospirillum ferrooxidans strain. Since T. ferrooxidans is an obligately acidophilic autotroph and E. coli is a heterotroph, ancestors of the Tn7-like transposons must have been active in a variety of physiologically different bacteria so that their descendants are now found in bacteria that occupy very different ecological niches.